Fulfillment of the Rights of Restitution for Victims of Sexual Violence Crimes in Ruling Number: 196/Pid.Sus/2023/Pn.Gtlo - Sahi, Rahman; Darmawati, Darmawati; Nusa, Apriyanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Sexual violence is a crime that must be eliminated because sexual crimes can cause psychological and/or physical suffering to victims that interfere with physical health. Therefore, it is necessary to make efforts for optimal mental and social recovery for Victims of Sexual Violence in accordance with existing regulations as a form of legal protection for victims. The purpose of this study is to realize the rights of Victims of Sexual Violence. This study uses a normative legal research method. The purpose and intent of this study is to analyze how judges consider the Fulfillment of Restitution Rights for Victims of Sexual Violence in their decisions, as regulated in Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, Government Regulation Number 43 of 2017 and Supreme Court Regulation Number 1 of 2022, by the panel of judges in the case of sexual violence Number 196/Pid.sus/2023/PN.Gtlo. Cases of sexual violence are rampant in our environment. The current Criminal Code (KUHP) only focuses on punishing the perpetrators and has not considered the best legal efforts for victims of sexual violence. This study aims to determine the implementation of restitution as the fulfillment of the rights of victims of sexual violence. This study is a normative study by looking at the implementation of restitution from the laws and regulations carried out by the Witness and Victim Protection Agency (LPSK). The results of this study indicate that the application for restitution can be submitted by the victim through LPSK along with the criminal process and even starting from the beginning of the investigation. The challenges faced by LPSK as an institution that facilitates restitution for victims of sexual violence include limited psychologists in several areas, lack of support from the community, and fulfillment of restitution rights that have not been implemented effectively. The obstacles experienced by law enforcement officers in implementing restitution for victims of sexual violence are that there has been no regulation of coercive efforts for perpetrators of sexual violence to pay restitution decided in court